Heideggerio technikos esmės sampratos recepcija „empirinio posūkio“ technikos filosofijoje - Mickevičius, Tomas Nemunas (Religija ir kultūra, 2017)
In this article some important aspects of Heidegger’s philosophy of technology is addressed. It is argued against Don Ihde’s observation that Heidegger’s philosophy of technology mostly concerns the large scale technological phenomena of industrial revolution – actually in Heidegger’s oeuvre we can find reflection on such micro-scale post-industrial technologies as cybernetics, biotechnologies etc. The critique of the essentialism of Heideggerian philosophy of technology by such authors as Andrew Feenberg, Don Ihde and Peter-Paul Verbeek is presented. It is suggested that earlier Heidegger’s concept of the essence of technology as “machination” (Machenschaft) is less susceptible to such criticism: whether technologies are exploitative and turning nature into “standing reserve”, or whether they are ecological and nature-friendly, whether they are understood as autonomous force, or democratically controlled process – it could be said that through contemporary technologies reality is increasingly turned into artifice and entities are revealed as makeable and producible.